Growth Characteristic of Fungus strain MGS-2 in a Defined Medium Containing Organic Acids Derived from Peat Soil - DIANA NURANI; KOESNANDAR KOESNANDAR (Indonesian Society for microbiology, 2013)
Some organic acids derived from lignin degradation in peat soil have significant role in lowering pH of peat soil and have phytotoxic effect for plant. A series of experiments has been conducted to decrease the amount of organic acids in peat soil by microbial treatment. The aim of the study was to characterize the growth of selected fungi using organic acids extracted from peat soil as a sole carbon source.The fungus strain MGS-2 was grown in a liquid medium containing various concentrations of organic acids extracted from peat soil, nitrogen and salt at initial pH of 3.8. The cell growth, pH of medium and the content of organic acids were analyzed. The identification of fungus MGS-2 was based on the 28S rDNA.The ability of Hypocrea sp. to degrade toxic organic acid derived from peat soil has never been reported. The organic acid and nitrogen optimum for the growth were 33.1 mN-NaOH and 2 g NH2SO4 per liter medium, respectively. The interaction between carbon and nitrogen source was found to be significantly influenced by the increment of pH medium, however this interaction did not effect to the cell growth and reduction of organic acids. The carbon source affected significantly to the cell growth and acid metabolism by fungus strain MGS-2 The fungus could not grow well in the medium without yeast exract, but grew well in the limitation of NH2SO4 , suggested that yeast extract was metabolized as nitrogen source. The optimum degradation of organic acids extracted from peat soil by MGS-2 was obtained at pH 3.8. Theseresult suggested that the cell mass production of MGS-2 can be performed in optimal defined medium utilizing organic acid derived from peat soil. Molecular identification revealed that the MGS-2 was closed to Hypocrea sp.